Complex outflow anatomy in left lateral lobe graft and modified venous reconstruction in pediatric living donor liver transplantation. (20th August 2014) - Benetatos, Nikolaos; Scalera, Irene; Isaac, John R.; Mirza, Darius F.; Muiesan, Paolo
Summary Hepatic venous outflow reconstruction is of critical significance in pediatric patients undergoing living donor liver transplantation. Accurate knowledge of the anatomical variations is important to obtain appropriate size segmental grafts. The diameter of the hepatic veins and the potential risk of complications at the level of the anastomosis require an adequate primary vascular reconstruction. We describe a venous outflow reconstruction technique, in a living related left lateral lobe graft, with unfavorable hepatic venous anatomy.